PENGARUH CITRA MEREK, KEPERCAYAAN RELIGIUS, DAN LABEL HALAL TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN MELALUI PERILAKU TERHADAP PRODUK DAN KESADARAN HALAL SEBAGAI VARIABEL INTERVENING (STUDI PADA PRODUK KOSMETIK) - Putri, Nadia Alesiana; Utami, Christina Whidya (ITB AAS Indonesia Surakarta, 2024)
Indonesia is one of the countries with largest muslim population in the world. The growth of halal industry in Indonesia has a very high potential in line with the high need for halal products, especially in the cosmetics industry. This research aims to determine the influence of brand image, religious beliefs, halal label, halal awareness, and behaviour towards products on consumer purchasing decisions. The research was conducted quantitatively. The samples for this research were muslim female respondents, cosmetics user, live in Wiyung West Surabaya, and must be in age range of 20 to 44 years old. The data were analysed using SEM-PLS method to explain the mediating relationship of the research variables. The results stated that brand image, religious beliefs, halal label, halal awareness of products can directly influence consumer purchasing decisions. Meanwhile, behaviour towards products does not directly influence consumer purchasing decisions. Behaviour towards products was unable to mediate brand image, religious beliefs and halal label on consumer purchasing decisions. Halal awareness was able to mediate religious beliefs and halal label on consumer purchasing decisions. However, halal awareness was not able to mediate brand image on consumer purchasing decisions